Critical success factors for public private partnership (PPP) implement in Malaysia - Ismail, Suhaiza (s.n, 2012)
The study aims to investigate the factors that attract the adoption of PPP in Malaysia. It also intends to examine the differences in the perceptions of government and private sector pertaining to the factors. A questionnaire survey was used to elicit the perceptions of public and private sectors on the attractive factors of PPP adoption in Malaysia